Diffusion bonding between high chromium white iron and austenitic stainless steel - Kurt, B.; Eroglu, M. (Maney Publishing, 2007)
In the present study, a high chromium white iron was diffusion bonded to an austenitic stainless steel, AISI 316L. The effects of bonding temperature and holding time at the reached temperature on microstructural developments across the joint region were investigated. After diffusion bonding, microstructural analysis including metallographic examination, energy dispersive X-ray ( EDX), X-ray, microhardness measurements and shear strength was performed. From the results, it was seen that bonding temperature with holding time was effective on the formation of carbide ( M3C) and width of the diffusion zone that affected the shear strength of the bonds.
Keywords: high chromium white iron; diffusion bonding; austenitic stainless steel; microstructure; hardness